Intelligent Hydroponic Control System with IoT and Fuzzy Logic on Kale Plants - Khairunnissa Zahran Ansyafa; Yana Nurrohman; Muhamad Al Habsy; Muhammad Fakhri Alauddin; Mahatmadi Ariq Mayangkara; Hafiz Agi Alfasih; Daryn Ramadhani Az Zahra; Aqim Try Kurnia; Arda Dwiyana; Inna Novianty (Journal of Applied Science, Technology & Humanities | JASTH, 2025)
The research in our project illustrates the application of hydroponic technology in Indonesia with a focus on nutrient control systems using the Internet of Things (IoT) and fuzzy logic for kale plants. Hydroponic methods such as Deep Flow Technic (DFT) are used to optimize plant growth in confined spaces, utilizing nutrient solutions that are controlled by pH and PPM. The system supports the efficiency and effectiveness of modern agriculture by monitoring environmental conditions such as temperature, humidity, and TDS values. This study shows that the system developed has an average error of 11.755% with an accuracy level of 88.65%. In addition, the system also managed to control the output of the nutrient pump with an error of 1.12% and an accuracy of 98.89%, as well as a water faucet with an average error of 0.47% and an accuracy of 99.75%. These results show the potential of IoT technology applications in increasing the productivity and sustainability of hydroponic agriculture in the future